Divergence and Diversity: Changing Chinese Perceptions of North Korea under Kim Jong-un. Issue 109 (2nd January 2018) - Chan, Che-po; Bridges, Brian
Abstract: A widely-held perception is that the image of North Korea among most Chinese people has changed from that of a socialist comrade and 'little brother' to an idiosyncratic, trouble-making neighbor. This research questions the homogeneity of Chinese people's viewpoints towards North Korea. Concepts of state and popular nationalism are used to examine differences and similarities between the Chinese state and its people in their perceptions and sentiments towards North Korea, mainly focusing on the period of succession from Kim Jong-il to Kim Jong-un. Examining online discussions representing Chinese popular nationalism demonstrated that Chinese netizens' political viewpoints are diversified along the ideological spectrum of left and right and that only the 'moderate left' netizens hold an image of North Korea which is close to that of their political authorities.